Effectiveness of digital media marketing strategy in improving marketing performance in SMEs: a study with service dominant logic theory perspective - Novandari, Weni; Suliyanto, Suliyanto; Wulandari, Siti Zulaikha; Yunanto, Ary; Yuwono, Tri (Business: Theory and Practice, 2026)
This study investigates the influence of digital media marketing strategy on brand innovation, performance, and overall marketing performance in Indonesia’s SME Creative Industry sector. The study examines how digital media brand innovation and digital media performance act as mediators in enhancing marketing outcomes, considering the impact of competition intensity and digital media strategic capability. Information was gathered via an internet-based survey focused on SMEs in the creative industry sector, including fashion, culinary, and crafts. The data were examined using the Partial Least Squares (PLS-SEM) methodology employing Smart PLS 3.0. The results indicate that the digital media marketing strategy impacts the digital media brand innovation and digital media performance, leading to a beneficial effect on marketing performance. This study highlights the need to implement an efficient digital media marketing strategy to enhance brand innovation and the performance of SMEs. The study underscores the intricate interaction between internal capacities and external market circumstances, underscoring the necessity for SMEs to adapt their strategies to sustain a competitive edge in the era of digitalization. Business practitioners recommended using digital media marketing strategy to enhance digital media brand innovation and maximize marketing performance.